Case report: an unstable wide QRS complexes tachycardia after ablation of a poster-septal accessory pathway. Issue 11 (March 2018) - Wang, Huan; Che, Xiaoru
Abstract: Introduction: Differentiation of wide QRS complex tachycardia required repeated electrophysiological stimuli and mapping. However, instability of tachycardia would increase the difficulty in differential diagnosis. Symptoms and Clinical findings: In this paper, we reported a wide QRS tachycardia following ablation of an atrioventricular reentrant tachycardia participated by a poster-septal accessory pathway. Limited differentiation strategy was performed because the wide QRS tachycardia was self-limited and with unstable hemodynamics. We analyzed the mechanism of the wide QRS tachycardia by only 4 beats ventricular overpacing. On the basis of the last ventricular pacing, an atypical atrioventricular nodal reentrant tachycardia was confirmed. Intervention and Outcomes: After slow-pathway modification, the wide QRS tachycardia was eliminated. Conclusion: It was an atypical atrial-ventricular node reentrant tachycardia with right bundle branch block. Reasonable analysis based on electrophysiological electrophysiologic knowledge was the basis of successful diagnosis and treatment.